2022
DOI: 10.3390/ani12131704
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Heifer Post-Weaning Intake Classification on Performance Measurements of Lactating and Non-Lactating Two-, Five-, and Eight-Year-Old Angus Beef Females

Abstract: Heifer post-weaning intake classification was utilized to evaluate subsequent intake and performance measurements of 2-, 5-, and 8year-old lactating and non-lactating Angus females. For both studies, heifers were categorized based on voluntary feed intake (expressed as g/kg BW) as either low (<−0.50 SD from the mean), average (± 0.50 SD from the mean), or high (>0.50 SD from the mean) within one year. Intake and production data of pregnant, non-lactating (n = 59; Study 1) and lactating, non-pregnant (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Additionally, Sowell et al [ 13 ] noted that herd structure and dynamics may also play a role in supplemental feeding, with older, dominant cattle over consuming supplement compared to younger, less dominant cattle. Moreover, Wellnitz et al [ 14 ] observed similar results with 5- and 8-year-old cows consuming more total feed than 2-year-old cows, regardless of pregnancy or lactation status. However, this was attributed to overall rumen capacity, which also may have played a role in the current study.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, Sowell et al [ 13 ] noted that herd structure and dynamics may also play a role in supplemental feeding, with older, dominant cattle over consuming supplement compared to younger, less dominant cattle. Moreover, Wellnitz et al [ 14 ] observed similar results with 5- and 8-year-old cows consuming more total feed than 2-year-old cows, regardless of pregnancy or lactation status. However, this was attributed to overall rumen capacity, which also may have played a role in the current study.…”
Section: Discussionmentioning
confidence: 72%